C-Reactive Protein and Matrix Metalloproteinase-9 are Associated with Outcome of Ischemic Stroke - Yenny Surjawan; Suryani As'ad; Teguh A S Ranakusuma; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: C-Reactive protein (CRP) and matrix metalloproteinase (MMP)-9 are inflammatory mediators that are often associated with the evolution of stroke. In this study, we aimed to find out whether concentration of these biomarkers were associated with the severity of discharge National Institute of Health Stroke Scale (NIHSS) in ischemic stroke patient.METHODS: In prospective stody, we involved 143 ischemic stroke patient who were admitted to hospital not more than 72 hours after the onset and who met the criteria. The concentration of CRP was assessed by High Sensitivity CRP reagent from Siemens and the concentration of MMP-9 was measure with Quantikine Human MMP-9 (total) Immunoassay from R&D. The outcome of stroke was determined by NIHSS score at discharge.RESULTS: There was a significant correlation between the CRP level and the severity of NIHSS at discharge (r = 0.288, p = 0.000). Subjects with intermediate/high level of CRP had a higher probability to have a moderate or even severe NIHSS (OR = 1.7, p = 0.004). Subjects with high MMP level showed a higher probability to have a severe NIHSS. CONCLUSION: The measurement of CRP and MMP-9 at 48-72 hours after stroke onset were associated with the severity of ischemic stroke based on NIHSS score at discharge. KEYWORDS: inflammation, CRP, MMP-9, discharged NIHSS